PERANCANGAN KOLEKSI PA’SURRA TORAYA SEBAGAI SELFSTATEMENT GAYA HIDUP WANITA URBAN - FEI SIEN JESICA; DEWI ISMA ARYANI; PETER MULJONO (Serat Rupa: Journal of Design, 2017)
Indonesia's cultural diversification, including the Toraja carving, has inspired the design of ready-to-wear deluxe fashion collection entitled "Pa'surra Toraya". Through the collection, Toraja carving, Pa'tedong and Pa'sekong Kandaure, are presented in a modern form acceptable among urban communities, especially women. Pa’su rra Toraya collection silhouette gives the ethnical impression for the enthusiasts of fashion with design elements inspired by Toraja traditional clothing. Toraja carving motif is applied to the clothing through print technique, beads (sequins), and flock screen-printing to reinforce the ethnic impression.The ready-to-wear deluxe collection, Pa'ssura Toraya, is intended for the public, especially the upper middle class women, 25-40 years old, characterized as smart, elegant, high-mobilized individuals who appreciate the local culture as a supporting fashion in semi-formal events. Keywords: engraving Toraja; ethnic; flock printing; modern; sequins